Airways changes related to air pollution exposure in wheezing children - Martins, P. C. (2019)
In this study, we aimed to evaluate the relationship between individual total exposure to air pollution and airway changes in a group of 51 wheezing children. Respiratory status was assessed four times (January 2006, June 2006, January 2007 and June 2007) during a 1-week period through a standardised questionnaire, spirometry, exhaled nitric oxide fraction and pH in exhaled breath condensate (EBC). Concentrations of particles with a 50% cut-off aerodynamic diameter of 10 µm (PM(10)), O(3), NO(2) and volatile organic compounds were estimated through direct measurements with an ad hoc device or air pollution modelling in the children's schools and at their homes in the same 4 weeks of the study. For each child, total exposure to the different air pollutants was estimated as a function of pollutant concentrations and daily activity patterns. Increasing total exposure to PM(10), NO(2), benzene, toluene and ethylbenzene was significantly associated with a decrease of forced expiratory volume in 1 s (FEV(1)) and with an increase of change in FEV(1). Increasing exposure to NO(2) and benzene was also related to a significant decrease of FEV(1)/forced vital capacity. Increasing exposure to PM(10), NO(2), benzene and ethylbenzene was associated with acidity of EBC. This study suggests an association in wheezing children between airway changes and total exposure to air pollutants, as estimated by taking into account the concentration in the various microenvironments attended by the children.